Seni Mural Sebagai Bentuk Ekspresi Nilai-Nilai Keislaman di Kota Salatiga, Indonesia - Ibrahim, Malik; Mubarok, Anis; Aeni, Melinda Sandra; Ramadhonah, Indah Siti; Adawiyah (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
This research was conducted with the aim to find out the representation of Islamic values found in mural art in Salatiga City, so that it can be useful for future researchers. This research is a descriptive qualitative research with semiotic analysis approach by referring to Roland Barthes' theory. The data collection technique in this research uses observation and documentation methods on the object of research. The observation method in this research is by looking at the mural images on the walls of Salatiga City directly, while the documentation method in this research is taking some photos of mural art images related to Islamic values. The result of this study shows that, in the art of drawing or painting on the walls of large